Interpretative, historical and virtual study of the San Francisco de Conchos Prison from the Camino Real de tierra adentro in Mexico - Carrillo Acosta, Roberto (2024)
It is vitally important to carry out studies that provide knowledge about history, since this is the basis for the interpretation and enhancement of heritage. In this case, given the scarce material evidence related to the Conchos prison, it is necessary to make a reconstruction or interpretation on a hypothetical level of its structure and spaces, to better understand its functioning, as well as its role in defense, but above all, in the settlement of Nueva Vizcaya. We worked based on our experience on the subject, reviewing the historiography and also through a comparative analysis between interpretation proposals, as well as making analogies with other contemporary fortifications. Thus, a satisfactory identification and reconstruction of the property was achieved, allowing clarity about its history and role within the occupation and pacification of colonial northern Mexico.